1998
DOI: 10.1093/rheumatology/37.7.779
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine expression and leucocyte infiltration in Sjogren's syndrome

Abstract: Chemokines expressed by ductal epithelial cells may attract circulating leucocytes, in particular CD4+ T cells, towards the site of inflammation, thereby orchestrating the influx of MN cells characteristically seen in MSGs in SS. Chemokines may be induced directly by a putative triggering agent for SS, or secondary to the release of pro-inflammatory cytokines produced by epithelial cells. These findings further implicate epithelial cells as playing a major role in the pathogenesis of SS and implicate chemokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
1
7

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 0 publications
3
60
1
7
Order By: Relevance
“…31 In addition, to evaluate the specific contribution of IkB-a phosphorylation to TACEinduced NF-kB activation in SGEC, we used the dominant negative super-repressor IkB-a, which disrupts phosphorylation and subsequent degradation, preventing NF-kB nuclear translocation. Following the discovery of proinflammatory cytokines accumulation in functionally and structurally damaged areas of the salivary glands, 3,6 we first assessed any differences in the level of gene expression of inflammatory mediators, such as cytokines/chemokines, in human SGECs treated with the anti-Ro/SSA Abs characterizing SS. The screening for abnormally expressed inflammatory mediators demonstrated that anti-Ro/SSA Abs enhanced the expression of CXC chemokines, CC chemokines, several ILs and their receptors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 In addition, to evaluate the specific contribution of IkB-a phosphorylation to TACEinduced NF-kB activation in SGEC, we used the dominant negative super-repressor IkB-a, which disrupts phosphorylation and subsequent degradation, preventing NF-kB nuclear translocation. Following the discovery of proinflammatory cytokines accumulation in functionally and structurally damaged areas of the salivary glands, 3,6 we first assessed any differences in the level of gene expression of inflammatory mediators, such as cytokines/chemokines, in human SGECs treated with the anti-Ro/SSA Abs characterizing SS. The screening for abnormally expressed inflammatory mediators demonstrated that anti-Ro/SSA Abs enhanced the expression of CXC chemokines, CC chemokines, several ILs and their receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Following the discovery of proinflammatory cytokines accumulation in functionally and structurally damaged areas of the salivary glands, 3,6 and its pathogenic significance in autoimmune diseases, 7,8 we assessed differences in the gene expression levels of inflammatory mediators, such as cytokines/chemokines, in human SGECs treated with the anti-Ro/SSA Abs that characterize SS. In anti-Ro/SSA Abs-treated SGEC we screened for abnormally expressed inflammatory mediators using RT 2 Profiler PCR arrays, a high-throughput technique, designed specifically to target major cytokines and chemokines.…”
Section: Tapi-1 Inhibits the Expression Of Inflammatorymentioning
confidence: 99%
See 1 more Smart Citation
“…We examined the mRNA levels of IL-6 and IL-8, major proinflammatory cytokines produced in MSG in SS patients [27][28][29][30], in MSG specimens. We also examined mRNA levels of IL-6 receptor and gp130 in MSG specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Chemokines and their corresponding chemokine receptors play an important role in lymphopoiesis, differentiation, homing, recirculation, and immune responses of lymphocyte subsets under physiologic and pathologic conditions (11)(12)(13)(14). The inflamed glands seen in primary SS have been shown to express a unique profile of adhesion molecules, cytokines, and chemokines, including overexpression of CXCL13 (B lymphocyte chemoattractant [BLC]; B cell-attracting chemokine 1 [BCA-1]) mRNA and protein, a central chemokine involved in B cell homing (15)(16)(17), as well as of CCL19, CCL18, CXCL9 (monokine induced by interferon-␥), and CXCL10 mRNA (17,18,19).…”
mentioning
confidence: 99%